An Analysis of Flouting Grice Maxims in Ellen DeGeneres Talk Show: A Pragmatic Study - Hadzik, Muhamad Irfan; Rozi, Fahrur; Pratama, Hendi (Institut Agama Islam Negeri Palopo, 2025)
This study discussed the importance of having good communication skills. The assessment standard refers to Grice's cooperative maxims as the basis for communication in order to achieve the purpose of communication itself. The speaker and the interlocutor must obey the maxims, if not obeyed then what is called a maxim violation occurs. The object of this study is to identify Grice’s cooperative maxims flouting in Ellen Talk Show and also analyze how maxims flouting trigger humor in Ellen Talk Show. This study used content analysis which was categorized into descriptive qualitative method. The data were taken by communication between Elias Phoenix and Ellen. The observation of study was taken on YouTube as data collection then identified by using Grice’s technique which analyzing maxims flouting into four items such as flouting of quantity, quality, relation and manner maxims. The results of study revealed that there were those all of maxims flouting in communication between Elias Phoenix and Ellen in Ellen Talk Show. The data in total were 47 utterances which were involved quantity maxim was 14 utterances (30%), quality maxim was 9 utterances (19%), relation maxim was 4 utterances (9%) and manner was 20 utterances (42%). The most of maxim flouting was manner maxim, 20 utterances (42%). Therefore, the data was analyzed that referring to how flouting of maxims trigger humor in Ellen Talk Show. Keywords: Flouting Grice Maxims, Cooperative principle, Humor, Elias Phoenix, Ellen Talk Show.